QUALITY FUNCTION DEPLOYMENT: A SYSTEMATIC APPROACH TO IMPROVING QUALITY AT RUMAH KEDUA COFFEE & SPACE - Erixon Halomoan Simamora; Imelda Junita (UPT Publikasi Ilmiah UNISBA, 2025)
Intensifying competition in the coffee shop sector requires improved service quality to maintain customer satisfaction. This study aims to evaluate the implementation of Quality Function Deployment (QFD) to enhance service quality at Rumah Kedua Coffee & Space. This descriptive study involved 155 respondents who completed a questionnaire with 21 service attributes/ items based on five SERVQUAL dimensions. Data analysis was conducted using the House of Quality (HoQ) matrix to determine improvement priorities. The majority of quality attributes exhibited negative service gaps, indicating that service quality did not meet customer expectations. Eleven attributes/ items with the largest gaps, representing the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, were identified as improvement priorities. Rumah Kedua Coffee & Space performed above expectations in only one attribute, namely ’employees’ personalized attention to customers’ (performance score of 3.74), which also had the highest overall weighting (5.47), indicating a significant influence on customer satisfaction. The HOQ analysis yielded 20 technical responses, with regular service excellence training receiving the highest absolute importance score (342) and a relative importance score of 25.6%, designating it as the highest priority for improvement. These findings provide strategic recommendations for achieving long-term competitiveness and service quality enhancement.